THE EFFECT OF NON-NUTRITIVE SUCKING (PACIFIER) ON THE BABY'S PAIN RESPONSE WHEN VENOUS BLOOD COLLECTION IS CARRIED OUT IN THE NEONATOLOGY ROOM OF LAVALETTE HOSPITAL - Frety Rahmasari; Director Trigantara; Nining Loura Sari (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Pacifiers are a safe and effective method that can provide comfort to newborns, especially when feeling sick. Neonatal babies born in the first 28 days often experience pain when undergoing treatment and treatment procedures, one of which is blood sampling. The use of non-nutritive sucking is very effective in reducing neonatal pain during invasive procedures or heel piercing. The research design used is quasi-experimental design. The sample consisted of 2 groups, namely the control group without intervention totaling 30 infants and the NNS intervention group totaling 30 infants. Data analysis technique using Independent sample t test. The results showed that the value of equal variances assumed is known as the sig value. (2-tailed) of 0.000 < 0.05. It can be concluded that there is an influence of the baby's NIPS scale by giving pacifier intervention to the baby during venous blood collection at the hospital. Lavalette.